Which shows the correct substitution of the values a, b, and c from the equation 1 = –2x + 3x2 + 1 into the quadratic formula? Quadratic formula:

Respuesta :

[tex]1=-2x+3x^2+1\\\\3x^2-2x+1-1=0\\\\3x^2-2x=0\\\\\boxed{a=3;\ b=-2;\ c=0}[/tex]

Answer:

[tex]a=3[/tex],  [tex]b=-2[/tex] and  [tex]c=0[/tex].

Step-by-step explanation:

We have been given an equation [tex]1=-2x+3x^2+1[/tex].

We know that a quadratic equation is in form [tex]ax^2+bx+c[/tex].

First of all, we need to convert our given equation in standard quadratic equation as shown:

[tex]1-1=-2x+3x^2+1-1[/tex]

[tex]0=-2x+3x^2[/tex]

[tex]-2x+3x^2=0[/tex]

[tex]3x^2-2x=0[/tex]

Upon comparing our equation with standard quadratic equation we can see that [tex]a=3[/tex],  [tex]b=-2[/tex] and  [tex]c=0[/tex].